COMPARATIVE ANALYSIS OF THE CONCEPT OF "LIFE" FOR THE WITNESSES OF THE HOLODOMOR AND THEIR DESCENDANTS - Yevchenko, Iryna; Masliuk, Andrii; Podolyak, Nataliia; Girchenko, Olena (International Journal of Psychosocial Rehabilitation, 2020)
The article contains the results of a comparative analysis of the associative series on the word-stimulus of "life" of famine witnesses and the descendants of famine witnesses in Ukraine. The scientific approaches to determining the features of traumatic situations, the consequences of traumatization have been considered. The analysis of modern scientific works devoted to the problems of studying traumatic events, suggests that "unprocessed" trauma adversely affects the personal development of the personality and, accordingly, the consequences of traumatization affect future generations. In order to identify the peculiarities of the perception of the concept of "life" by the descendants of famine witnesses, an empirical study was conducted in which three groups of descendants of the famine witnesses were identified: potential children of the witnesses to the famine (1st generation), potential grandchildren of the witnesses to the famine (2nd generation), potential right-wing victims (3rd generation). The analyzed results were compared with the results of the witnesses to the famine on the word-stimulus "life", which were obtained by one of the authors during the previous psychological research. According to the empirical research, we can say that the associative field of the concept of "life" in the witnesses to the famine and their descendants has significant differences. For the witnesses to famine and the descendants in the 1st generation (potential children of the witnesses to the famine), the associations with the word stimulus "life" have a more negative load, that is, the witnesses to the famine and the descendants in the 1st generation perceive life as complicated, more prone to disappointment. The representatives of the II and III generations have managed to rethink their attitude towards life, so they are attuned to a positive perception of life events. The third generation pays the most attention to the temporal life perspective, although age peculiarities contribute to a more acute attitude to life events. According to the results of the study, we cannot unambiguously state the reduction of the traumatic impact of the events of the famine in Ukraine with each future generation, therefore additional research is needed.